Attractiveness of the Czech Republic for IT business - competition with other European countries - Borovik, Sofiia; Semenenko, Vadim; San José Iglesias, Rafael; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2022)
The aim of this bachelor thesis is to identify the opportunities and weaknesses that the Czech Republic has for the development of IT business and attracting talent from this field. A secondary objective of the work is to propose steps that the Czech Republic should take in order to develop the IT industry faster and more efficiently in terms of attracting IT investments, companies and talents. The first part is theoretical, which provides information about the ICT sector and describes the role of ICT in the economic development of the country. This part also discusses the factors affecting the attractiveness of the country and provides theoretically represents the PEST and SWOT strategic analyses. The empirical part of the work is focused on the analysis of the business environment of the Czech Republic by the PEST method, the analysis of the ICT sector of the country and its comparison with other European countries is carried out. An important part of the analysis is interviews with ICT experts, which provide valuable information about the attractiveness of the Czech Republic, the opportunities and weaknesses of its IT market, and the business environment. SWOT analysis of the Czech ICT market based on data obtained, recommendations and conclusions is offered as the last one.
Vedoucí práce: Vadim Semenenko
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2022
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2022
Způsob přístupu: Internet
Keywords: mezinárodní obchod [obor bakal. práce]; bakalářské práce; bachelor's theses